2022
DOI: 10.3389/fchem.2022.884105
|View full text |Cite
|
Sign up to set email alerts
|

The High-Effective Catalytic Degradation of Benzo[a]pyrene by Mn-Corrolazine Regulated by Oriented External Electric Field: Insight From DFT Study

Abstract: The degradation of BaP into hydroxybenzo[a]pyrene by Mn-corrolazine and its regulation by an oriented external electronic field (OEEF) were systematically studied using first-principle calculations. Extensive density function calculations showed that the degradation of BaP into hydroxybenzo[a]pyrene by Mn-corrolazine occurs via a three-step process in the absence of OEEF, in which a more toxic and stable epoxide intermediate is generated. However, upon application of OEEF along the intrinsic Mn-O reaction axis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…31–40 Due to their unique structural characteristics, high-valent metal corrolazines are widely used in different fields. 41–47 Goldberg's experiments and our theoretical studies indicate that the high-valent O–Mn-corrolazine can oxidize organic substrates directly using O 2 . Recently, our group reported that O–Fe-corrolazine can catalyze methane oxidation under mild conditions through the rebound mechanism and found that the reaction barrier can be effectively regulated by OEEFs.…”
Section: Introductionmentioning
confidence: 81%
“…31–40 Due to their unique structural characteristics, high-valent metal corrolazines are widely used in different fields. 41–47 Goldberg's experiments and our theoretical studies indicate that the high-valent O–Mn-corrolazine can oxidize organic substrates directly using O 2 . Recently, our group reported that O–Fe-corrolazine can catalyze methane oxidation under mild conditions through the rebound mechanism and found that the reaction barrier can be effectively regulated by OEEFs.…”
Section: Introductionmentioning
confidence: 81%
“…In contrast, the more Zr oxo -cOOH sites on (cOH) m /UiO-66-H, the lower the activity to produce CH 3 OH is via the rebound reaction. 20,75 The mechanism of H-atom radical/ abstraction methane activation [78][79][80] on Zr-oxo nodes is also proposed (Fig. S6 †).…”
Section: Evolution Of Adsorbed Oxygenic Species On Zr-oxo Nodesmentioning
confidence: 99%
“…Following the cleavage of both the C-H bond of CH 4 and O-the O bond of cOOH* (TS3``), the newly generated cOH quickly rebounds to cCH 3 to form CH 3 OH (P3). [75][76][77] The corresponding potential energy prole indicates that this process requires a relatively high energy barrier of 1.01 eV with an reaction energy of −2.83 eV.…”
Section: Evolution Of Adsorbed Oxygenic Species On Zr-oxo Nodesmentioning
confidence: 99%